Valorization of dredged sediments: Influence of sediment content on mechanical properties and environmental behavior - Bader Bouzar; Yannick Mamindy-Pajany; Nor-edine Abriak; Mahfoud Benzerzour (Green Technologies and Sustainability)
This study explores the valorization of marine sediments as a substitute for natural sand in cementitious matrices for maritime applications. The results indicate that increasing sediment content leads to higher water-accessible porosity, resulting in materials that are less dense than the reference ones. However, mechanical performance remains acceptable for many maritime applications, even at high substitution rates exceeding 50%. The microscopic analysis confirms that the sediment is mainly composed of quartz — similar to natural sand — the​ physical properties of the two materials diverge considerably. The sediment exhibits higher porosity, greater water absorption, and lower bulk density, largely due to its finer particle size distribution and more heterogeneous morphology. The sediment morphology influences both the fresh and hardened states of the mortars, particularly impacting porosity and workability. Compressive strength tests identified the optimal formulation containing 60% sediment, achieving compressive strengths of 17 MPa at 7 days, 31 MPa at 28 days, and 35 MPa at 90 days in freshwater curing, with comparable results in saltwater. The material also demonstrated a robust dynamic modulus, suitable for long-term applications. Environmental assessments, including leaching tests performed according to NF EN 12457-2, confirmed that the sediment-based mortars are inert. All concentrations of trace metals and anions remained well below the regulatory thresholds for inert waste, even after 90 days of curing. The results further show that the sediment does not release harmful pollutants in marine or terrestrial environments, making it environmentally safe.